(untitled) (Maritime Park: Journal of Maritime Technology and Society, 2023)
Abstract: The Port Singapore Authority (PSA) have a big role in sea transportation in Indonesia, whoever average 50 big vessels per day are tendered at the wharf of Singapore port for loading and unloading thousands of containers, so if Singapore port is congested for several hours the impact will make the crowded of sailing schedule for many vessels. Last week suddenly without any announcement Singapore port reported a problem with their port facilities and so their system, therefore many vessels were anchorages for several days about 4-6 days at the outer of the port for waiting time to tender. This accident makes the sea transport system by feeder service Indonesia-Singapore and vice versa re-scheduled. The impact for export-import activities from and to Indonesia was trouble because many can’t call on time even omitted. For several years or starting in 1985 Indonesian Shipping lines depend on Singapore port as an international hub port that will through cargoes to the destination port. They chose Singapore port because there are complete port facilities and a container system, nobody knows that crisis so will bome at Singapore as the biggest port in South East Asia. So now suggested to all of Indonesian shipping and Government to make a new big port as functions like Singapore port as an International hub port.